Cilengitide restrains the osteoclast‐like bone resorbing activity of myeloma plasma cells. (5th January 2016) - Tucci, Marco; Stucci, Stefania; Felici, Claudia; Cafforio, Paola; Resta, Leonardo; Rossi, Roberta; Silvestris, Franco
Summary: Cilengitide (CLG) is an inhibitor of both αv β3 and αv β5 integrins, with a defined anti‐tumour effect in glioblastoma. Pre‐clinical studies demonstrate its ability to restrain the bone resorbing property of metastatic osteotropic tumours and we have previously shown that the disablement of αv β3 in multiple myeloma (MM) plasma cells results in exhaustion of their in vitro osteoclast (OC)‐like activity on bone substrate. Here, we investigated the effect of CLG on this functional property of MM cells. Both αv β3 and αv β5 were measured on primary marrow MM cells from 19 patients, and the effect of CLG on proliferation, apoptosis and adhesion was investigated in parallel with MM cell lines and OCs from healthy donors. In addition, the effect of CLG on the capability of malignant plasma cells to produce erosive lacunae on calcium phosphate was explored in relation to the activation of intracellular kinases of molecular pathways of both integrins. Ultrastructural microscopy was used to evaluate the morphological changes in MM cells due to the effect of CLG on cell adhesion. The data from our study demonstrate that CLG restrains the bone resorbing function of MM cells by disabling their adhesion properties. Further investigations in pre‐clinical studies of osteotropic tumours are warranted.